7‐1: Invited Paper: UDC Technology for OLED Display. Issue 1 (28th June 2022) - Lou, Jun-hui; Zhang, Lu; Ge, Lin
Abstract : UDC (Under‐Display Camera) technology is a technology breakthrough that can most likely solve the contradiction between the display integrity and front camera. It can improve the integrity of the display and the proportion of display screen. This paper analyzes the difficulties and challenges of the UDC technology, presents the progress of each key technical point and explores potential solutions. In the end, the paper introduces the UDC technology development and productions in Visionox Company.